Erotismo e religião em Georges Bataille - Strozzi, Gina Valbão (2007)
The objective of the present work is to determine the use and conception, as well as the relation with each other, of the terms Erotism and Religion in the writings of Georges Bataille, emphasising Erotism: Death and Sensuality, The Tears of Eros and Inner Experience, texts which concentrate the main dimensions of his oeuvre. In these, the author exposes the epistemological element of erotic experiences and their religious foundations. Bataille composes an encounter between religion and sexuality, a meeting that defies the action of human continuity and discontinuity, superseding and condemning the being. Thus, life and death meet by means of the discovery of erotism and religion, being erotism the inner life substance of humans, deeply identifying them with religious experiences. The adopted approach for the present work was approximative and problem-focused, intended to dare to discover the essential meaning of the bataillian erotica, reaching an understanding. With no pre-conceived rigour, a journey throughout his works is hereby proposed. We go from the theoretical influences that caused the meeting of the aforementioned concepts to a critical and geographical interpretation of the chosen body of documents, favouring the conceptual structure of Erotism and Religion and their correlated terms: interdiction, transgression, sacrifice, death, life, continuity and discontinuity. Finally, the central focus of this study is on the concepts of Erotism and Religion and their inter-relation within the experience of mystical ecstasy